This The Implementation Of The Imla Method In Maharoh Kitabah Learning Reviewed From A Constructivist Perspective At The Modern Islamic Boarding School Al-Abraar - harahap, desi hariyanti; Hilmi, Danial; harahap , arpin aminuddin (Al-Himam, 2025)
This study aims to describe the implementation of the Imlā' method in learning Arabic writing skills (maharah al-kitābah) at the Al-Abraar Modern Islamic Boarding School and analyze its suitability from a constructivistic perspective. The research approach used is descriptive qualitative with data collection techniques in the form of in-depth interviews, participatory observation, and documentation of santri writing results. The results show that the Imlā' method is applied systematically through the stages of mastering grammatical concepts, structured dictation exercises, and insyā' writing. This learning process involves the active role of the teacher as a facilitator who provides guidance (scaffolding) and correction on an ongoing basis, so that students are able to build independence in thinking and writing. From the viewpoint of constructivism, the Imlā' method reflects contextual and reflective learning, where knowledge is actively constructed through direct experience and social interaction. Documentation of writing results shows significant progress in spelling accuracy, sentence structure, and understanding of nahwu-sharaf rules. The findings show that the Imlā' method is not only effective in improving technical writing skills, but also relevant to meaningful learning approaches that focus learners as active subjects in the learning process.